2013
DOI: 10.1093/aob/mct245
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary history of sea barley (Hordeum marinum) revealed by comparative physical mapping of repetitive DNA

Abstract: The tetraploid forms of gussoneanum appear to have come about through a cross between a diploid gussoneanum progenitor and a second, related-but unidentified-diploid ancestor. The results reveal the genome structure of the different H. marinum taxa and demonstrate the allopolyploid origin of the tetraploid forms of gussoneanum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…The subtelomeric pSc119.2 satellite DNA tended to spread towards new interstitial sites during the diversification of the most primitive form of the genus Secale towards the most advanced taxa [Cuadrado and Jouve, 2002]. This highly repetitive sequence has supported events of interstitialization also in Hordeum [Carmona et al, 2013b]. Differences in the rates of sequence change were found between interstitial, slower and subtelomeric repeats .…”
Section: Chromosome-specific and Interstitial Satellite Dnasmentioning
confidence: 89%
“…The subtelomeric pSc119.2 satellite DNA tended to spread towards new interstitial sites during the diversification of the most primitive form of the genus Secale towards the most advanced taxa [Cuadrado and Jouve, 2002]. This highly repetitive sequence has supported events of interstitialization also in Hordeum [Carmona et al, 2013b]. Differences in the rates of sequence change were found between interstitial, slower and subtelomeric repeats .…”
Section: Chromosome-specific and Interstitial Satellite Dnasmentioning
confidence: 89%
“…Additional differences between Hordeum bogdanii and Hordeum vulgare can be seen in the distribution patterns of AAT, GCC, CAG, 45S rDNA, 5S rDNA and pSc119.2. Physical mapping of a few sequences in Hordeum marinum (Xa genome) showed that AAC and AAG produced intense and rich patterns of multiple SSR signals that were particularly concentrated in the pericentromeric region and that ACT and CAT were weakly distributed (Carmona et al 2013b). The pSc119.2 repeat produced sub-telomeric signals on nearly all chromosomes in Hordeum marinum (Taketa et al 2000); however, fewer of these signals were present in Hordeum bogdanii .…”
Section: Discussionmentioning
confidence: 99%
“…The pSc119.2 repeat produced sub-telomeric signals on nearly all chromosomes in Hordeum marinum (Taketa et al 2000); however, fewer of these signals were present in Hordeum bogdanii . Karyotype analysis of diploid Hordeum murinum (Xu) showed that AG produced intense signals around the centromere in four chromosome pairs and that AAG produced more rich and intense signals than AAC, ACT, and CAT in pericentromeric regions (Cuadrado et al 2013, Carmona et al 2013b). In addition, no pSc119.2 hybridization signals were detected in diploid Hordeum murinum (Taketa et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations